Density, abundance and extractive potential of the mangrove crab, Ucides cordatus (Linnaeus, 1763) (Brachyura, Ocypodidae): subsidies for fishery management - Pinheiro, Marcelo Antonio Amaro [UNESP]; Souza, Marcelo R.; Santos, Luciana C. M.; Fontes, Roberto F. C. [UNESP] (FapUNIFESP (SciELO), 2018)
Ucides cordatus is a relevant fishery resource of Brazilian mangroves and requires legal normative to sustainable use based on stock assessment and management. This study evaluated some population parameters (structure, density, abundance, fishery potential and stock) of this crab species in Brazil Southeast (São Paulo, State), discussing the use of the results to delineate fishery management strategies. Density was monthly evaluated (September 1998 to August 1999), using five sample quadrats of 2×2 m. Density (ind.m-2) was indirectly estimated by counting the opened (with biogenic activity) and closed galleries, and contrasted with flooding level by tides using the vertical distribution of macroalgae in the base of trees. Density of U. cordatus ranges from 2 to 11 ind.m-2 (6±2 ind.m-2) and statistical difference occurred among monthly means (F=11.58; p=0.000). The relationship density vs. tidal flooding indicated a decrease of U. cordatus density in mangroves with higher levels of tidal flooding (r=-0.94; p=0.001). The total abundance of U. cordatus was estimated in 63.7 millions of crabs in 10.61 km2, with a reduction of 34.9% due to total mortality discount. Estimates like that are uncommon in literature, and could be used for fishery forecasts, allowing improvement by the introduction of new variables to be known in the future.
Keywords: Crab; Crustacean; Fishery; Management; Mangrove; Population